The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physreve.84.051133
|View full text |Cite
|
Sign up to set email alerts
|

Block voter model: Phase diagram and critical behavior

Abstract: We introduce and study the block voter model with noise on two-dimensional square lattices using Monte Carlo simulations and finite-size scaling techniques. The model is defined by an outflow dynamics where a central set of N(PCS) spins, here denoted by persuasive cluster spins (PCS), tries to influence the opinion of their neighboring counterparts. We consider the collective behavior of the entire system with varying PCS size. When N(PCS)>2, the system exhibits an order-disorder phase transition at a critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The BVM is defined by an outflow dynamics where a central set of N PCS spins, denoted by persuasive cluster spins (PCS), tries to influence the opinion of their neighboring counterparts. It is shown that the effects of increasing the size of the persuasive cluster are the reduction of the critical amplitudes and the increment of the ordered region in the phase diagram [7]. Therefore, within the context of the present study, the range of interaction parameter is defined by the number of spins N PCS inside the persuasive cluster (that is, = N PCS ).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The BVM is defined by an outflow dynamics where a central set of N PCS spins, denoted by persuasive cluster spins (PCS), tries to influence the opinion of their neighboring counterparts. It is shown that the effects of increasing the size of the persuasive cluster are the reduction of the critical amplitudes and the increment of the ordered region in the phase diagram [7]. Therefore, within the context of the present study, the range of interaction parameter is defined by the number of spins N PCS inside the persuasive cluster (that is, = N PCS ).…”
Section: Introductionmentioning
confidence: 91%
“…The phase diagram of the model in the q − N PCS parameter space was reported in Ref. [7]. From the results for q c , we simulate the BVM on regular square lattices of linear length L = 100,160,180,200, and 300, considering periodic boundary conditions and asynchronous update.…”
Section: A Regular Latticementioning
confidence: 99%
See 3 more Smart Citations